Problem solving fundamentals : a framework to anticipate, analyze, and resolve challenges. (O'Reilly Media, Inc., 2023)
Problems. We are plagued with them. Some we see coming, but others sneak up on us. Do youfeel like you need to put out fires on a daily basis and sometimes are left with little time to get toyour core responsibilities? The ability to meet problems head on in the most efficient and sustainable fashion is a core skill for any professional wanting to make their mark. Having thetools to be able to solve problems effectively increases your productivity, streamlines workflow,and prepares you to take on new roles and responsibilities. Join Zina O'Leary as she walks you through how to tackle issues before they become problems, how to identify problems so that they can be addressed, and how to analyze problems so thatyou can successfully deal with them. After this course you will be able to resolve problems in asustainable fashion that satisfies a range of stakeholders. What you'll learn and how you can apply it Control issues before they become problems Identify problems as they arise Analyze problems from a variety of perspectives Efficiently and effectively engage in problem resolution This course is for you because... You're an individual contributor in your organization and you want to learn how to tackleissues before they become complex and potentially expensive problems. You manage a team and you need to be able to analyze and solve problems in the mostefficient and effective manner possible. You're a leader within your organization and you want to embed solid problem solvingskills in your workforce. You want to become a better problem solver.